Efficiency Assessment of Using Flammable Compounds from Water Treatment and Methanol Production Waste for Plasma Synthesis of Iron-Containing Pigments; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Shekhovtsova A. P. Anastasia (2016, 2016)
Title screen